INTEGRATED SIMULATION IN ARCHITECTURE, ENGINEERING, AND CONSTRUCTION FOR INNOVATIVE AND SUSTAINABLE STRUCTURAL DESIGN - ,C., Brugev; , B.G., Kovachec (JoDA Journal of Digital Architecture, 2025)
The construction industry faces significant challenges related to cost efficiency, delays, and design complexity. This study aims to highlight the importance of utilizing integrated simulation in architecture, civil engineering, and construction to enhance structural safety, sustainability, and performance. The methodology involves digital modeling using the 3DEXPERIENCE platform and Abaqus software to analyze loads, deformations, and the impact of structural failures in bridges and high-rise buildings. Simulation results demonstrate that this approach can predict critical stress, detect early design weaknesses, and optimize material usage by up to 10%. Case studies such as the Sun Valley Structure and the CCTV Building in Beijing confirm the effectiveness of simulation in supporting complex designs. Consequently, this approach offers a holistic solution that promotes project efficiency and structural innovation in the modern construction era.